Quasi-two-dimensional simulation of an ion-implanted GaAs MESFET photodetector - Madheswaran M.; Rajamani V.; Chakrabarti P. (My University, 2025)
A quasi-two-dimensional numerical model of an optically gated GaAs metal semiconductor field-effect transistor (MESFET) has been developed for the characterization of the device as a photodetector. The model considers the channel to be nonuniformly doped. The model involves the solution of a 1-D Poisson's equation, and takes into account the field-dependent mobility of the carriers in the channel for computation of the current. It has been found that, in a short-channel MESFET photodetector, the drain current saturation is caused by the velocity saturation of the carriers rather than pinch off. The photocurrent gain, responsivity, and the input RC time constant of an ion-implanted GaAs MESFET having a semitransparent metal gate have been estimated numerically on the basis of the model. The device has a high photocurrent gain, a high responsivity, and a low-input RC time constant at an operating wavelength of 0.85 μm.